Program Kegiatan Infak Jum’at Dalam Mengembangkan Nilai – Nilai Akhlak Anak Di Tk Aisyiyah Bustanul Athfal Cabang Binjai Kota - Nurhayati Nurhayati; Nurul Bariyah; Widya Khairunnisa; Zannatunnisya Zannatunnisya; Sri Susanti (Journal on Education, 2024)
Values ​​are something that is most important or valuable for humans and is also the essence of life. Value is a normative pattern, which determines the desired behavior for a system that is related to the surrounding environment without distinguishing between its functions and parts. Values ​​prioritize the functioning of maintaining the pattern of the social system. Religious morals are the most important, most valuable and most basic thing for humans because apart from fulfilling human instincts, they are also able to lead humans to their ultimate goal, namely serving their God. Based on the research results, it can be concluded that the definition of Moral Values ​​is habits of behavior referring to general rules regarding right - wrong or good and bad that apply in wider society to instill a sense of faith in children. Habituation is a process of activities carried out repeatedly which aims to make individuals accustomed to behaving, behaving and thinking in accordance with predetermined goals. The aim of the routine Friday Infaq Program in schools is to form relatively permanent student attitudes and behavior, namely the growth of caring attitudes towards others, high social values, sensitivity to the social environment and strong social interactions. This can happen because it is done repeatedly. both in the learning process and outside the learning process.